International business : Environments and operations - Daniels, John D. (Pearson Eduacation, 2004)
Contents: background for international business; comparative environmental frameworks; theories and intitutions: trade and investment; world financial environment; the dynamics of international business government relationships; operations: overlaying tactical alternatives,...